British Gynaecological Cancer Society (BGCS) cervical cancer guidelines: Recommendations for practice. (January 2021) - Reed, Nick; Balega, Janos; Barwick, Tara; Buckley, Lynn; Burton, Kevin; Eminowicz, Gemma; Forrest, Jenny; Ganesan, Raji; Harrand, Rosie; Holland, Cathrine; Howe, Tamara; Ind, Thomas; et al.
Abstract: Cervix cancer in many countries is declining and screening programmes and immunisation will reduce the incidence in the next few decades. This guideline attempts to cover management of invasive disease reflecting diagnosis and imaging including new imaging and sentinel lymph node biopsies. Smaller volume disease is usually managed surgically whereas advanced disease is treated with (chemo)- radiation. It also includes discussion of fertility sparing procedures. Practices are changing frequently for all aspects of care usually in attempts to reduce complications and improve quality of life. The management of advanced disease is treated by chemotherapy and the use of newer agents is also discussed. Other sections discuss specialist situations such as cancer in pregnancy, rare cervical tumours, late effects and supportive measures and fertility preserving approaches.